FROM SYMBOLIC SUSTAINABILITY TO SUBSTANTIVE JUSTICE: STRENGTHENING LOCAL GOVERNMENT OVERSIGHT OF GREENWASHING IN INDONESIA - I Gusti Ayu Eviani Yuliantari (Jurnal Hukum Progresif, 2026)
Greenwashing has emerged as a significant challenge in environmental governance, as sustainability claims made by business actors do not always reflect their actual environmental performance. In Indonesia, this problem is further complicated by regulatory gaps, fragmented environmental oversight, and the changing distribution of authority between central and local governments. This study examines how the principle of substantive justice can provide a normative foundation for strengthening local governments’ authority to oversee greenwashing practices and analyses its implementation within Indonesia’s regional autonomy framework. The research employs a doctrinal legal method employing statutory, conceptual, case, and interpretive approaches. Primary and secondary legal materials are analysed qualitatively by examining constitutional principles, environmental legislation, regional government regulations, and theories of substantive justice, responsive law, and environmental governance. The study finds that greenwashing is not merely a problem of misleading corporate communication, but also represents a distortion of environmental information that may undermine the constitutional right to a good and healthy environment. From the perspective of substantive justice, environmental supervision should extend beyond formal and administrative compliance toward factual verification of environmental claims, ecological impacts, and corporate practices. Local governments possess strategic advantages because of their proximity to local communities, ecosystems, and business activities, yet their supervisory role remains constrained by increasingly centralised environmental approval mechanisms. Strengthening local authority should therefore be pursued through functional decentralisation and collaborative governance rather than a complete transfer of regulatory power. Local governments should be empowered to conduct on-site verification, validate environmental information, assess socio-ecological impacts, involve affected communities, and issue binding technical recommendations within environmental supervision processes. The study contributes a legal framework that integrates substantive justice, regional autonomy, and greenwashing oversight – positioning local governments as key actors in ensuring environmental transparency, accountability, and the substantive protection of ecological and community interests.